VALIDATION OF ASSESSMENT INSTRUMENTS FOR INTEGRATED SCIENCE LEARNING ON THE ABILITY OF STUDENT USING RASCH MODEL - Marantika Lia Kristyasari; Sri Yamtinah (EDUSAINS, 2022)
The Computerized Two Tier Multiple Choice (CTTMC) instrument has been created to mesure the bility of student in Integrated Science learning. This research was conducted to produce empirical evidence regarding the validity of the TTMC instrument using the Rasch Model analysis thorugh the Winstep program. A total of 283 junior high school students in the city of Surakarta were the research subjects. This assessment instrument consists of 20 questions. Statistical analysis was performed using the Rasch model. The results of the analysis show that in general, this assessment instrument can explain 40.7% of the variance that appears in each group of respondents. As many as 85% of the questions were declared fit and 15% of the questions still needed to be improved. Of the 283 participants, 13,4% had an ability misfit, 13,8% were included in the upper outlier, and 72,8% of the participants had an infit ability. Thus, that the assessment of Integrated Science SMP learning, in general, can be carried out using this instrument. How To Cite: Kristyasari, M.L., Yamtinah, S. (2022). Validation Of Assessment Instruments For Integrated Science Learning On The Ability Of Student Using Rasch Model. EDUSAINS, 14 (1) : 24-33.